(3NdGUI GdCNHGQ aj CMhGd GdfHi GdeNJGQs - (3eMehO CafOj GdCScOGQj, GdCScOGQj,J (B1036 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Yde GdEfSGf eG de jYde hLYd BOe NdjaI ai GdYGde hbOQ ai GdCRd eG JCNQ heG JbOe s
(3BNQgG (B:s
(3aYdjc HGdGLJgGO ai GeQ GdOjf hGJHGY SfI SjO GdeQSdjf hcf Ydi SjQ GdUGdMjf GdcGedjf hGYHO QHc MJi jGJjc Gdjbjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B827s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B717s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs